"And they gave me a shot, it really hurt" – Evaluative content in investigative interviews with young children. (November 2017) - Fängström, Karin; Sarkadi, Anna; Lucas, Steven; Calam, Rachel; Eriksson, Maria
Abstract: Research is scarce on the suitability of the evidence-based components of child investigative interviews when used in non-forensic contexts, such as social work or school, particularly in relation to children's reports on emotional content. This explorative study investigated to what extent a structured forensic interview protocol aids children in verbalizing negative emotional experiences of distress or discomfort. To do this we assessed and compared children's displayed distress during a video-recorded health visit with the verbalized distress in interviews 2–4 weeks later about this visit. The children, aged 4 and 5 years (N = 26), were interviewed with a forensic interview protocol. The recorded visits were coded for level of distress and children's statements regarding distress along with the interviewer questions preceding them were analyzed qualitatively. The results showed that 46% of the 4-year-olds and 39% of the 5-year-olds displayed discomfort or distress during their health visit. In the interviews, open-ended questions were posed to all children. These questions were sufficient to aid only some children (n = 6) to share evaluative content. However, none of the children who displayed distress or discomfort during the visit verbalized such experiences after an invitation only. Most children who described negative experiences did so in response to evaluative questions. The results suggest that more research is warranted on how and when evaluative questions should be posed and whether this differs depending on severity of experience or the child's age. The need for protocol development and its suitability when used in other fields of practice is discussed. Highlights: In social work and risk assessment children's emotional experiences are important. Study of children's emotional accounts in investigative interviews is scarce. Open-ended questions are often insufficient to elicit young children's emotional experiences. Evaluative questions, e.g. "How did it feel", aid children to verbalize emotions. The need for guidelines on questioning about emotional reactions is discussed.